Indigenous Knowledge Systems in Environmental Governance in Canada - McGregor, Deborah (KULA)

(untitled) (University of Victoria Libraries, 2021)
This contribution addresses key issues around the application of Indigenous knowledge in contexts where such knowledge is neither generated nor held (academy, industry, governments, etc.). Effective models for the ethical incorporation of Indigenous knowledge into environmental governance in Canada have remained elusive despite decades of attempts. The predominant research paradigm of “incorporating” Indigenous knowledge into environmental governance is one of extraction by the external interests who seek to include specific aspects of such knowledge in their undertakings. This approach continues to fail because Indigenous knowledge exists as an integral component of Indigenous Knowledge Systems (IKS). It is often hollow and potentially damaging to consider any knowledge without understanding the societal systems and peoples that produced it. Indigenous knowledge is not just “knowledge” (a noun) but a way of life, something that must be lived (a verb) in order to be understood. Indigenous knowledge is inseparable from the people who hold and live this knowledge. Although government policy and legislation have evolved in attempts to treat Indigenous knowledge more holistically, the overriding paradigm of extraction remains essentially unchanged. Even the most recent frameworks will meet with limited success as a result. Appropriate and effective inclusion of Indigenous knowledge requires recognition of the systems that support it, which in turn necessitates support for Indigenous self-determination.